Firm performance, corporate governance, and top executive turnover in Japan - Kang, Jun-Koo; Shivdasani, Anil (Journal of Financial Economics, 1995)
We examine the role of corporate governance mechanisms during top executive turnover in Japanese corporations. Consistent with evidence from U.S. data, the likelihood of nonroutine turnover is significantly related to industry-adjusted return on assets, excess stock returns, and negative operating income, but is not related to industry performance. The sensitivity of nonroutine turnover to earnings performance is higher for firms with ties to a main bank than for firms without such ties. Outside succession in Japan is more likely for firms with large shareholders and a main bank relationship. We document performance improvements subsequent to nonroutine turnover and outside succession.